Pengaruh Konsentrasi Sukrosa terhadap Karakteristik Minuman Probiotik Sari Buah Nanas Madu (Ananas comosus (L.) Merr) Terfermentasi dengan Isolat Lactobacillus rhamnosus SKG34 - Krisna Devi, Ni Ketut Ayu; Nocianitri, Komang Ayu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
This research was conducted to determine the effect of sucrose concentration on the characteristics of fermented honey pineapple (Ananas comosus (L.) Merr) probiotic drink with Lactobacillus rhamnosus SKG34 and to determine the concentration of sucrose that produced the best characteristics. This research used a Completely Randomized Design (CRD) with factors of sucrose concentration that consist of 6 levels (0%, 3%, 6%, 9%, 12%, and 15%). Each treatment was repeated 3 times resulting in 18 experimental units. The data were analyzed by analysis descriptive for total LAB and pH, Analysis of Variance (ANOVA) for total sugar, total acid, and sensory evaluation. The result of the analysis shows that total sugar, total acid, and sensory evaluation brought a significant effect on the concentration of sucrose. Thus, a further test was conducted on those variables using Duncan Multiple Range Test (DMRT). The result shows that sucrose concentration can increase the total LAB and decrease pH. The addition of sucrose concentration had a significant effect on total sugar, total acid, hedonic of color and taste, score of sour and sweet taste, and overall acceptance. However, it didn’t affect hedonic of aroma and score of aroma. The concentration of 9% sucrose produced the best characteristics of fermented honey pineapple (Ananas comosus (L.) Merr) probiotic drink with total LAB 10,31 Log CFU/ml, total sugar 14,24%, total acid 0,38%, pH 3,36, the color, aroma, and taste were liked, the aroma typical pineapple strong, slightly sour and sweet taste were liked, and overall acceptance was liked.